The enfacement illusion in autism spectrum disorder: How interpersonal multisensory stimulation influences facial recognition of the self - Deltort, Nicolas; Swendsen, Joël; Bouvard, Manuel; Cazalets, Jean-René; Amestoy, Anouck (Frontiers in Psychiatry, 2022)
At its most basic level, the sense of self is built upon awareness of one’s body and the face holds special significance as the individual’s most important and distinctive physical feature. Multimodal sensory integration is pivotal to experiencing one’s own body as a coherent visual “self” representation is formed and maintained by matching felt and observed sensorimotor experiences in the mirror. While difficulties in individual facial identity recognition and in both self-referential cognition and empathy are frequently reported in individuals with autism spectrum disorder (ASD), studying the effect of multimodal sensory stimulation in this population is of relevant interest. The present study investigates for the first time the specific effect on Interpersonal Multisensory Stimulation (IMS) on face self-recognition in a sample of 30 adults with (n=15) and without (n=15) ASD, matched on age and sex. The results demonstrate atypical self-face recognition and absence of IMS effects (enfacement illusion) in adults with ASD compared to controls, indicating that multisensory integration failed in updating cognitive representations of one’s own face among persons with this disorder. The results are discussed in the light of other findings indicating alterations in body enfacement illusion and automatic imitation in ASD as well as in the context of the theories of procedural perception and multisensory integration alterations.